Dai Training During the Covid-19 Pandemic at Krembung District - Muhammad Anwar Syihab; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
Muhammadiyah education is a learning system in fostering and developing human personality through science and Islam as well as Muhammadiyah organizations. The purpose of this study was to determine the cadre activities of Muhammadiyah students during the Covid-19 pandemic. In the framework of preparing competent cadres as successors to the Muhammadiyah syarikat which was carried out by the Muhammadiyah Student Association (IPM) Tulangan sub-district. Through the Muhammadiyah Student Dai Training (PDPM) during the Covid-19 pandemic, many cadres from villages in the Tulangan sub-district participated in this PDPM. This study uses a qualitative description. The results of the analysis of the PDPM activities carried out by the IPM in Tulangan sub-district were successfully carried out. However, there were shortcomings in this activity, namely: 1) Time efficiency, 2) Participants decreased, 3) It was difficult to contact the participants.